La vulnerabilidad del desarrollo sostenible medida a través de la huella ecológica. - Urtiaga, Carlos Porroche; Gracia, Ana Anguas; Ramos, Eduardo Mir; Santamaría, Rosana Garrido (Medicina Naturista)
Sustainable development is the most important measure for protecting the environment. The existence of websites that tell us energy expenditure, water, transport and waste in each household help us to know the environmental footprint we leave so that they can improve the sustainability of the planet. Our goal is to analyze and disclose the term ecological footprint and the rules governing control of biodiversity, performing a literature review in scientific basis. In addition, we have performed an analysis of a website that measures the ecological footprint.